Mechanical performance of self-sealing cementitious composites - Sharifah Umairah Binte Syed Gani (Nanyang Technological University, 2023)
Due to increase concern for sustainability and safety of building structures, there has been many studies and development of self-sealing and self-healing concrete. It is common understanding that concrete, despite being the most used man-made material, its low tensile strength makes it susceptible to cracks. Although there are many developments of self-sealing concretes, there is still room for development to ensure that initial mechanical performance of concrete is not compromised despite its ability to repair cracks and restore water permeability. Therefore, the aim of this study is to find out how self-sealing capsules affect the initial mechanical performance of cementitious composites as well as its mechanical performance after self- sealing. The main method used to prepare the self-sealing capsules would the encapsulation of sodium alginate by granulation of polyethylene glycol. The tests that would be carried out would be compression and flexural test as well as microscopy analysis.